Narratives of resistance: (Re) Telling the story of the HIV/AIDS movement – Because the lives and legacies of Black, Indigenous, and People of Colour communities depend on it - Wilson, Ciann Larose; Flicker, Sarah; Restoule, Jean-Paul; Furman, Ellis (Health Tomorrow: Interdisciplinarity and Internationality, 2017)
Centering the narratives of the intersectional struggles within the HIV movement for Indigenous sovereignty, Black and People of Colour liberation, and LGBTQ rights tirelessly fought for by Black, Indigenous, and People of Colour communities legitimates their lives and legacies within the movement; and the relevance of a focused response to the HIV epidemic that continues to wreak devastation in these communities. The recent political push for a post-HIV era solely centers the realities of middle-class white, gay men and has genocidal implications for Black, Indigenous, and People of Colour communities. Keywords: HIV/AIDS; Black, Indigenous and People of Colour communities; Social Movements; Narrative